Low switching frequency modulation for generalized three-phase multilevel inverters geared toward Grid Codes compliance - Mohammed Setti; Mohamed Cherkaoui (Institute of Advanced Engineering and Science, 2021)
In this paper, a generalized three-phase multilevel power inverter (MLI) structure is proposed under asymmetric configurations. The operating mode and the switching combinations are briefly exposed according to the parity of the number of direct current (DC) voltage sources in use. Subsequently, the proposed topology is evaluated in terms of commonly used factors and then benchmarked against some of the state-of the-art cascaded MLIs featuring multiple DC voltage sources (MDCS-CMLIs) while putting emphasis on the reduction of power switching devices. Moreover, a new nearest level control (NLC)-based modulation technique is designed for the purpose of better comply with some quality grid codes, namely the European EN 50160 and the International IEC 61000-2-12. The identification of the optimal control thresholds is realized by a constrained optimization algorithm (e.g., particle swarm optimization (PSO)) which is implemented in python script and validated through SIMULINK fast fourier transform (FFT) analysis tool. Lastly, the harmonic performance of the proposed technique is compared side-by-side with that of the conventional NLC scheme and exhibits significant reduction in harmonic distortion.